Natural and anthropogenic factors of landslide processes within the slopes of the loess plateau - Vynnykov, Yuriy; Kharchenko, Maksym; Yaholnyk, Andrii; Lystopad, Serhii (Academic journal Industrial Machine Building Civil Engineering, 2022)
The authors of the article analyzed the geomorphological, geological and hydrogeological features of the structure of the slopes of river valleys within the boundaries of the loess plateau under anthropogenic influence. The main factors of the occurrence of landslide processes were highlighted. The geomorphological structure of the slope was analyzed taking into account the dynamics of landslide processes. The influence of the hydrogeological regime on the reduction of the mechanical properties of soils within the basins was evaluated. The authors analyzed the genesis of loess, loess, and deluvial-proluvial deposits. A spatial information model of the slope array has been compiled. Its stability of the massif of the slope was evaluated taking into account the geological structure, hydrogeological factor, structural parameters of soils and their changes within the basins
Keywords: relief; genesis; loess rock; slope; landslide; basin; soil strength; structural cohesion; stress-deformed state; stability